2016
DOI: 10.4149/av_2016_04_354
|View full text |Cite
|
Sign up to set email alerts
|

High molecular polymorphism of the hypervariable region in the VP2 gene of Aleutian mink disease virus

Abstract: Summary. -Parvoviruses exhibit extreme genetic plasticity. The VP2 protein, containing a hypervariable region, is of particular importance. A single nucleotide change in this part of the genome and its effect on the amino acid sequence may significantly affect the range of infected hosts, tropism for specific tissues, or virulence. The high polymorphism in the hypervariable region can be exploited for phylogenetic analysis. The aim of this study was to analyze the polymorphism of the VP2 hypervariable region i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Our research, based on polymorphism in the sequence encoding the VP2 protein, showed eight closely related variants of the pathogen. High variability on a single farm has been confirmed by previous analyses conducted in Poland [27], as well as results reported by Canuti et al [28], who observed considerable variation in the pathogen resulting from the high stocking density on the farm. Polymorphism in the nucleotide sequence of the VP2 protein of the virus may translate into changes in its structure and functionality and thus result in a varied immune response in the host.…”
Section: Discussionsupporting
confidence: 81%
“…Our research, based on polymorphism in the sequence encoding the VP2 protein, showed eight closely related variants of the pathogen. High variability on a single farm has been confirmed by previous analyses conducted in Poland [27], as well as results reported by Canuti et al [28], who observed considerable variation in the pathogen resulting from the high stocking density on the farm. Polymorphism in the nucleotide sequence of the VP2 protein of the virus may translate into changes in its structure and functionality and thus result in a varied immune response in the host.…”
Section: Discussionsupporting
confidence: 81%
“…The VP2 protein, containing a hypervariable region and epitopic regions, is largely responsible for the antigenic properties of the pathogen and its spectrum of infection [22,23]. In the case of amdoviruses, which include AMDV, the variation between isolates is particularly high even within individual farms [24].…”
Section: Discussionmentioning
confidence: 99%
“…Given the resources of bioinformatic databases of AMDV sequences, it seems reasonable to select primers that fl ank the most frequently deposited sequences, in order to allow global analysis of the epidemiology of the virus. The primers used in our research have previously been used in single reactions in a study on phylogenetic analyses between AMDV isolates [28,15]. Phylogentic analysis based on the sequence coding NS1 protein confi rmed that obtained variants belong to the clade with the highly pathogenic strains Utah, and ADV-LN1-3 [29] and are distant from non-pathogenic AMDV-G, which forms separate clade.…”
Section: Discussionmentioning
confidence: 78%
“…High genetic variability is also observed in the case of the Aleutian virus, which belongs to the family Parvoviridae. There are reports of numerous variants occurring on a single farm [15], or even co-infections of one host with several variants [16]. Not only can high genetic variability cause changes in antigenic properties and the appearance of falsenegative results in serological methods [17], but due to the occurrence of mutations at primer binding sites, it can result in decreased effi cacy or even a lack of amplifi cation in diagnostics based on classic PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation